2019
DOI: 10.1039/c9fo00521h
|View full text |Cite
|
Sign up to set email alerts
|

Starch digestion kinetics of extruded reformed rice is changed in different ways with added protein or fiber

Abstract: Extruded rice with added 20% soy protein isolate or corn bran showed two-phase [(k1/k2) high/low, low/high] kinetic patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Generally, the presence of protein can reduce the starch digestibility, stimulate humans to secrete insulin, as well as reduce insulin resistance and the glycaemic response level, thereby reducing the GI of food, which is conducive to reducing the risk of T2DM (Na‐Nakorn et al ., 2019; Sidorova et al ., 2018; Camps et al ., 2018). Additionally, the addition of protein‐rich ingredients, e.g .…”
Section: Effects Of Adding Whole Legumes Flour On the Quality And Gi ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the presence of protein can reduce the starch digestibility, stimulate humans to secrete insulin, as well as reduce insulin resistance and the glycaemic response level, thereby reducing the GI of food, which is conducive to reducing the risk of T2DM (Na‐Nakorn et al ., 2019; Sidorova et al ., 2018; Camps et al ., 2018). Additionally, the addition of protein‐rich ingredients, e.g .…”
Section: Effects Of Adding Whole Legumes Flour On the Quality And Gi ...mentioning
confidence: 99%
“…As is known to all, rice is a major cereal crop in people's lives, it has been proven to be a raw material for various indispensable essential nutrients and healthy extruded products (Dalbhagat et al ., 2019). At the same time, it is generally the staple food in the world, especially in Asia, since it has made an enormous contribution to meeting the nutritional needs of consumers and providing energy for humans (Na‐Nakorn et al ., 2019; Silva et al ., 2020). Yet, the GI of rice is generally high meaning the glucose is rapidly released during digestion in the small intestine (Goebel et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] White rice is considered a high glycemic index (GI) food and extruded reformed rice has been reported to be a lower GI product. [ 41 ] De Pilli et al. [ 42 ] also reported that extrusion cooking promoted amylose‐lipid complexes' formation.…”
Section: Technologiesmentioning
confidence: 99%
“…Extrusion cooking combined with a moderate level of protein or fiber protein has also been reported to yield mid-range GI prod- ucts that could be suitable for diabetics or others desiring to control blood glucose response. [41] White rice is considered a high glycemic index (GI) food and extruded reformed rice has been reported to be a lower GI product. [41] De Pilli et al [42] also reported that extrusion cooking promoted amylose-lipid complexes' formation.…”
Section: Extrusionmentioning
confidence: 99%
See 1 more Smart Citation